Metabolic reprogramming by miRNAs in the tumor microenvironment: Focused on immunometabolism - Alshahrani, Shadia Hamoud; Ibrahim, Yousif Saleh; Jalil, Abduladheem Turki; Altoum, Abdelgadir Alamin; Achmad, Harun; Zabibah, Rahman S.; Gabr, Gamal A.; Ramírez-Coronel, Andrés Alexis; Alameri, Ameer A.; Qasim, Qutaiba A.; Karampoor, Sajad; Mirzaei, Rasoul (Frontiers in Oncology, 2022)
MicroRNAs (miRNAs) are emerging as a significant modulator of immunity, and their abnormal expression/activity has been linked to numerous human disorders, including cancer. It is now known that miRNAs potentially modulate the production of several metabolic processes in tumor-associated immune cells and indirectly via different metabolic enzymes that affect tumor-associated signaling cascades. For instance, Let-7 has been identified as a crucial modulator for the long-lasting survival of CD8+ T cells (naive phenotypes) in cancer by altering their metabolism. Furthermore, in T cells, it has been found that enhancer of zeste homolog 2 (EZH2) expression is controlled via glycolytic metabolism through miRNAs in patients with ovarian cancer. On the other hand, immunometabolism has shown us that cellular metabolic reactions and processes not only generate ATP and biosynthetic intermediates but also modulate the immune system and inflammatory processes. Based on recent studies, new and encouraging approaches to cancer involving the modification of miRNAs in immune cell metabolism are currently being investigated, providing insight into promising targets for therapeutic strategies based on the pivotal role of immunometabolism in cancer. Throughout this overview, we explore and describe the significance of miRNAs in cancer and immune cell metabolism.